A Need Analysis of ESP For Office Administration Program at SMK Negeri 2 Purworejo in the Academic Year of 2018/2019 - Putri Yuni Mentari (Journal of English Education and Teaching, 2019)
The objectives of the study are to describe the textbooks used by English teachers at present and its quality for Office Administration program; to explain to what extend do the teachers and the students need of ESP-Content based English materials in their English textbook and  to describeEnglish skills and the material of ESP for Office Administration students. To get the data for the study, two sets of questionnaire were used. First was questionnaire for teacher, second questionnaire for students. The steps for analyzing the data were (1) Selecting the data from the result of the questionnaire ,(2) Identifying the data about student’s need in the ESP material and the English textbook, (3) Classifying the data from the teacher and student’s answer,(4) Calculating percentage of answers in the questionnaire,(5) Making conclusion.The result of the study shows that  teacher used two English textbooks in teaching English. The English textbooks have a good quality, in term of the learners’ activities, the picture and illustration. However the material in the textbook was not appropriate with the student need in Office Administration Program. The students and the teacher need English textbook which contains with the ESP. The English textbook should contain the items based the students need and theEnglish skill needed by the students in Office Administration Program.